ChatGPT: A catalyst for evolutionary change in language learning experience / Siti Nurshafezan Ahmad - Ahmad, Siti Nurshafezan (Office of the Deputy Vice-Chancellor (Research & Innovation), 2023)
The use of AI in education has recently taken precedence with the recent emergence of ChatGPT, a language generative model where data is trained to adhere to human instructions. ChatGPT marks the beginning of continuous evolution in language learning in the 21st century. What makes ChatGPT compelling is its ability to provide written responses close to human cognitive responses. It can generate logical and complex human-like responses of various genres; from a simple response such as English essays and summaries, to more complex response such as analyses. Dahmen et al. (2023) defined ChatGPT as a language generation model developed by Open AI that can generate text based on the input it receives. Baidoo-Anu and Ansah (2023) concluded that what ChatGPT generates indicates how interactional and able ChatGPT is in carrying human-like conversation on various topics, as well as in generating content that is creative. Risang Baskara and Mukarto (2023) described ChatGPT's abilities as producing responses that are coherent and contextually suitable based on various stimulus, comprehending natural language prompts, and supplying answers and summaries, especially in higher education, by offering significant potentials in language learning and instruction. Nevertheless, it is also fair to say that it raises concerns among language educators over its human-like written responses, reflecting its ability to "think" and take away learners' language productive and receptive skills. Although the ability of an AI to churn human-like responses warrants concern and caution, it needs to be welcomed with an open mind.